Methods for delineating the land leveling range in land consolidationand rehabilitationprojects - D.J. Zhang; S.P. Yuan; W. Peng; F.F. Yu (Lowland Technology International, 2017)
Although elevation surveying has been widely used in land consolidation and Rehabilitation projects in China, the delineation of land leveling range still mainly depends on a person's subjective decision and therefore suffers from a lack of scientific criteria. Spatial analysis based on GIS is applied to provide a quantitative foundation for land leveling. Firstly, a grid map of DEM is obtained through spatial interpolation using elevation data; secondly, DEM data is disposed by two different methods based on sliding window arithmetic, i.e., neighborhood analysis method and local singularity analysis technique; at last, the range for land leveling is delineated by using these two methods respectively. This research shows that both methods can effectively identify the land leveling area with little differences and thus they could be used as quantitative tools for the planning and design of land levelling in land consolidation and Rehabilitation projects